Preliminary results of the study on the reasons of the Hai Hau erosion phenomenon - Ninh, Pham Van; Vinh, Phan Ngoc; Hung, Nguyen Manh; Manh, Dinh Van (Vietnam Journal of Mechanics, 2007)
Overall the evolution process of the Red River Delta based on the maps and historical data resulted in a fact that before the 20th century all the Nam Dinh coastline was attributed to accumulation. Then started the erosion process at Xuan Thuydistrict and from the period of 1935 - 1965 the most severe erosion was contributed in the stretch from Ha Lan to Hai Trieu, 1965 - 1990 in Hai Chinh - Hai Hoa, 1990 - 2005 in the middle part of Hai Chinh - Hai Thinh (Hai Hau district). The adjoining stretches were suffered from not severe erosion. At the same time, the Ba Lat mouth is advanced to the sea and to the North and South direction by the time with a very high rate. The first task of the mathematical modeling of coastal line evolution of Hai Hau is to evaluate this important historical marked periods e. g. to model the coastal line at the periods before 1900, 1935 - 1965; 1965 - 1990; 1990 - 2005. The tasks is very complicated and time and working labors consuming. In the paper, the primarily results of the above mentioned simulations (as waves, currents, sediments transports and bottom - coastal lines evolution) has been shown. Based on the obtained results, there is a strong correlation between the protrusion magnitude and the southward moving of the erosion areas.